Hội tụ về tốc độ tăng trưởng kinh tế của các tỉnh, thành phố trực thuộc Trung ương - Lý Đại , Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The paper examines the determinants of convergence in economic growth (relative convergence) across central provinces and cities in Vietnam. The methodology combines the endogenous growth theory, analyzed in Aghion and Howitt (2008), with empirical evidence on a data sample of 63 provinces over 2010–2019. The result shows that only for the central provinces and cities with high-quality human capital (i.e, higher than a threshold implied by empirical evidence), the economic growth rate raises for a closer proximity to world technology frontier, or the convergence of economic growth happens. For other provinces and cities, there exists the divergence of economic growth (i.e, the economic growth rate reduces for a closer proximity to world technology frontier). Among the central cities, Hai Phong has an outstanding growth rate by exploring the backwardness advantage, based on the combination of a high proximity to world technology frontier with an improvement of institutional quality. The result suggests that the human capital should receive highest investment on the policy architecture in the future.